The Man Who Couldn't Sleep - Stringer, Arthur, 1874-1950; Snapp, Frank (Salt Lake City, UT : Project Gutenberg, 2010)
"The Man Who Couldn't Sleep" by Arthur Stringer is a novel written in the early 20th century. The story centers around Witter Kerfoot, a Canadian author who has found success writing tales set in Alaska, despite his inexperience with the region. As his personal life and career begin to crumble under the weight of his deceitful past, Kerfoot faces the unraveling of his sanity and self-worth, prompting him to navigate a world of societal expectations and personal ambition. The opening of the novel introduces Witter Kerfoot, who reflects on his life as an author and the precarious facade he has managed to maintain among New York's elite. As he grapples with a growing sense of failure and insomnia, the narrative reveals his internal struggles while immersing him in a complicated web of relationships and aspirations, particularly regarding his love for Mary Lockwood, a wealthy woman who challenges him to pursue more meaningful work. The tension escalates when Kerfoot inadvertently gets embroiled in a violent incident, leading to a night of turmoil and self-discovery that will force him to confront the specter of his own life choices. (This is an automatically generated summary.)
Release date is 2010-11-25
Produced by Al Haines
Keywords: New York (N.Y.) -- Fiction; Adventure stories; Crime -- Fiction